Critical Role of Synovial Tissue–Resident Macrophage and Fibroblast Subsets in the Persistence of Joint Inflammation - Kemble, Samuel; Croft, Adam P. (Frontiers in Immunology, 2021)
Rheumatoid arthritis (RA) is a chronic prototypic immune-mediated inflammatory disease which is characterized by persistent synovial inflammation, leading to progressive joint destruction. Whilst the introduction of targeted biological drugs has led to a step change in the management of RA, 30-40% of patients do not respond adequately to these treatments, regardless of the mechanism of action of the drug used (ceiling of therapeutic response). In addition, many patients who acheive clinical remission, quickly relapse following the withdrawal of treatment. These observations suggest the existence of additional pathways of disease persistence that remain to be identified and targeted therapeutically. A major barrier for the identification of therapeutic targets and successful clinical translation is the limited understanding of the cellular mechanisms that operate within the synovial microenvironment to sustain joint inflammation. Recent insights into the heterogeneity of tissue resident synovial cells, including macropahges and fibroblasts has revealed distinct subsets of these cells that differentially regulate specific aspects of inflammatory joint pathology, paving the way for targeted interventions to specially modulate the behaviour of these cells. In this review, we will discuss the phenotypic and functional heterogeneity of tissue resident synovial cells and how this cellular diversity contributes to joint inflammation. We discuss how critical interactions between tissue resident cell types regulate the disease state by establishing critical cellular checkpoints within the synovium designed to suppress inflamamtion and restore joint homeostasis. We propose that failure of these cellular checkpoints leads to the emergence of imprinted pathogenic fibroblast cell states that drive the persistence of joint inflammation. Finally, we discuss therapeutic strategies that could be employed to specifically target pathogenic subsets of fibroblasts in RA.